RUNNER-TIP CULTURE OF STRAWBERRY (Fragaria x ananassa Duch) GROWN ON SEVERAL SHOOT-INDUCTION MEDIUM - Rindang Dwiyani; Hestin Yuswanti; Ni Nyoman Ari Mayadewi; Yuyun Fitriani (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2020)
A research regarding “Runner-tip culture of strawberry (Fragaria x ananassa Duch) Grown on Several Shoot-induction Medium” has been investigated. The objective of the research was to find out the most suitable medium for shoot production from runner-tip culture of strawberry at establishment step of micropropagation. The research was laid out in a Completely Randomized Design, 4 treatments of medium type for shoot induction and 10 replication, each was represented by one (1) bottle with 6-8 explants. The treatments were summarized as follows: T1 = MS ; T2 = MS + 2 ppm BAP + 0.01 ppm NAA; T3 = MS + 1 ppm of TDZ; T4 = WPM + 2 ppm BAP + 0.01 ppm NAA. The parameters observed were days of the bud emergence, the average number of shoots per explant, and the average number of leaves per explant. It can be concluded that among medium used in the current research, the medium of MS added with 1 ppm thidiazuron (TDZ) was the most suitable medium for shoot production of strawberry from the explant of runner-tips. The treatment was resulted in the earliest time of bud emergence, and producing the highest number of shoots and leaves.